Reproductive profile of Etawah crossbred does fed flushing diet containing different kinds of plant oil and animal fat - D. A., Astuti; L., Khotijah; Maidin, M. S.; P., Nugroho (Asian Network for Scientific Information, 2020)
Background and Objective: Reproduction system is affected by nutrient status of the animal. Flushing is one of reproduction program where the animal should give good quality diet. This study was aimed to evaluate etawah crossbred does reproduction performance giving flushing diet with different fat sources. The fat of plant oils are sunflower and flaxseed and from animal oils are tallow and Lemuru fish. Materials and Methods: Twenty four of Etawah crossbred does (average body weight 33.83±3.70 kg) were used in this experiment by using completely randomized block design. There are four treatments with four animals of each treatment. The treatments were flushing diet containing 5% sunflower oil (R1), 5.2% flaxseed oil (R2), 5.3% tallow (R3) and 5% Lemuru fish oil (R4). Treatment was given three weeks before and two weeks after matting, following 2 weeks before partus. During pregnant, the does were given basal diet (ratio concentrate:napier grass was 70:30). Body condition score, nutrient status, blood metabolite and hormone and also performance reproduction were evaluated. Results: The nutrient consumption was same in all treatment. Blood glucose were same in all treatments but the highest blood cholesterol was in R3 during estrus and in R4 during mid gestation. The highest plasma estradiol was in R1 during early gestation, while the highest plasma progesterone was in R2 during late gestation. Litter size and birth weight were same in all treatment, while the highest total embryo was in R2 treatment. Conclusion: It is concluded that flaxseed oil for flushing diet was significantly increased number of total embryo.